Consequences of Salesforce Motivation (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2018)
Salesforce motivation has been found to have important consequences for salespeople as well as  sales organization. This study analyzes the consequences of salesforce motivation based on the  review of studies. The review of studies showed that motivation has an impact on salesforce  behavioural and outcome performance, sales territory performance, job satisfaction, adaptive  selling, salespeoples' effort, role conflict, role ambiguity, burnout, salesperson's effective listening  behavior and managerial trust. Based on the findings, research implications are stated.
Keywords: Salesforce motivation; Salespeople; Sales organizations